Implementation of a Web-Based Theater Show Inventory Borrowing System - Raihan Arief Wicaksana (Publikasi Indonesia, 2025)
Inventory management is one of the important aspects of theatrical performance execution, where several important elements support the needs of the show. Within the scope of Zone 3 Cirebon, there are various theater organizations or groups spread across various campuses. In this study, several campuses were selected as samples: Universitas Muhammadiyah Cirebon (through the